10‐2: Invited Paper: Unified Analysis of Transient and Steady‐State Electroluminescence –Establishing an Analytical Formalism for OLED Charge Balance. Issue 1 (May 2017) - Hershey, Kyle W.; Holmes, Russell J.
Abstract : Organic light‐emitting devices (OLEDs) can exhibit an efficiency roll‐off under high current excitation that has been previously modeled using bimolecular quenching. The corresponding transient electroluminescence behavior has not been as effectively treated. Here, we reproduce both the steady‐state and transient regimes by introducing into the analysis a dynamic polaron population. This approach permits a rigorous definition of OLED charge balance in terms of dynamics as the exciton formation efficiency.